Sympatric or micro-allopatric speciation in a glacial lake? Genomic islands support neither. Issue 12 (27th December 2022) - Sun, Ning; Yang, Liandong; Tian, Fei; Zeng, Honghui; He, Ziwen; Zhao, Kai; Wang, Cheng; Meng, Minghui; Feng, Chenguang; Fang, Chengchi; Lv, Wenqi; Bo, Jing; et al.
Abstract: Apparent cases of sympatric speciation may actually be due to micro-allopatric or micro-parapatric speciation. One way to distinguish between these models is to examine the existence and nature of genomic islands of divergence, wherein divergent DNA segments are interspersed with low-divergence segments. Such islands should be rare or absent under micro-allopatric speciation but common in cases of speciation with gene flow. Sympatric divergence of endemic fishes is known from isolated saline, crater, postglacial, and ancient lakes. Two morphologically distinct cyprinid fishes, Gymnocypris eckloni scoliostomus (GS) and G. eckloni eckloni (GE), in a small glacial lake on the Qinghai–Tibet Plateau, Lake Sunmcuo, match the biogeographic criteria of sympatric speciation. In this study, we examined genome-wide variation in 46 individuals from these two groups. The divergence time between the GS and GE lineages was estimated to be 20–60 Kya. We identified 54 large genomic islands (≥100 kb) of speciation, which accounted for 89.4% of the total length of all genomic islands. These islands harboured divergent genes related to olfactory receptors and olfaction signals that may play important roles in food selection and assortative mating in fishes. Although the genomic islands clearly indicated speciation with gene flow and rejected micro-allopatric speciation, they were too large to support the hypothesis of sympatric speciation. Theoretical and recent empirical studies suggested that continual gene flow in sympatry should give rise to many small genomic islands (as small as a few kilobases in size). Thus, the observed pattern is consistent with the extensive evidence on parapatric speciation, in which adjacent habitats facilitate divergent selection but also permit gene flow during speciation. We suggest that many, if not most, of the reported cases of sympatric speciation are likely to be micro-parapatric speciation.